COURSE OF UVEITIS IN PATIENTS WITH ANKYLOSING SPONDYLITIS - A. A. Godzenko; A. G. Bochkova; O. A. Rumyantseva; I. Yu. Razumova; V. V. Badokin; Sh. F. Erdes (Научно-практическая ревматология)
Relapsing uveitis is a serious problem for patients with ankylosing spondylitis (AS). Tumor necrosis factor-α  inhibitors significantly reduce the frequency of uveitis attacks in AS patients, but they are not always available. In this connection, it is appropriate  to evaluate the effect of traditional  disease-modifying antirheumatic drugs on the course of uveitis in AS.Objective: to compare the frequency of uveitis attacks in AS during combined therapy using sulfasalazine (SULF)  and nonsteroidal  anti-inflammatory drugs (NSAIDs)  versus monotherapy with NSAIDs.Subjects and methods. A total of 111 patients with significant AS who had at least one uveitis attack during the disease were examined. 49 subjects received combined therapy including SULF 2 grams daily and NSAIDs for at least 1 year. Six of the 49 patients were noted to have frequently relapsing uveitis (above 3 episodes yearly); 43 had no more than 3 ones per year. The remaining 62 patients took NSAIDs only throughout  the follow-up period. Nine of them had an average of 3 uveitis attacks per year; 53 had no more than 3 ones per year. Out of the 49 patients receiving combined therapy with NSAIDs and SULF,  23 took NSAIDs only at least 1 year before SULF use; 10 of them were observed to have frequent relapses in that period and 13 had three or fewer episodes.Results and discussion. The entire group showed an average of 2.06±2.04 uveitis attacks per year during monotherapy with NSAIDs and 1.41±1.83 attacks yearly during combined therapy with NSAIDs and SULF (p = 0.08). Among the patients with less than 3 uveitis attacks per year, the mean number of episodes was significantly fewer during combined therapy than during NSAID monotherapy: 0.99±0.87 and 1.37±0.91,  respectively (p = 0.04). Among those with frequently relapsing uveitis (more than 3 attacks per year), the mean number of episodes yearly was not significantly different during NSAID monotherapy and combined therapy: 5.7±2.5 and 5.5±2.7,  respectively (p = 0.9). In a subgroup of patients receiving sequentially NSAID monotherapy and combined therapy with NSADs and SULF,  13 patients with three or fewer baseline attacks per year displayed a significant reduction  in the frequency of episodes from 1.92±0.96 to 0.4±0.44 (p = 0.00003). During combined therapy versus monotherapy, 10 patients with frequently relapsing uveitis (over 3 episodes yearly) exhibited an insignificant reduction  in the number of relapses from 5.9±3.02 to 5.33±1.1 (p = 0.6).Conclusion. Combined therapy with SULF and NSAIDs does not substantially affect the frequency of uveitis episodes in AS patients with frequently relapsing uveitis (above 3 attacks per year), but significantly reduces the number of episodes among patients with its mild course (less than 3 attacks yearly).